Flame retardant polyester fiber and preparation method thereof

By using polyester slices, modified flame retardant and modified aramid fibers, blending extrusion and spinning processes, flame retardant polyester fibers with good antibacterial properties and flame retardant properties are prepared, and the flame retardant in the prior art is solved. Problems of insufficient high-temperature flame retardant properties of agent agglomeration and polyester fibers.

CN118773769BActive Publication Date: 2025-02-07ZHEJIANG ROYALCOVER TEXTILE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411042852.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-02-07
Estimated Expiration
2044-07-31

AI Technical Summary

Technical Problem

In the prior art, flame retardant is prone to agglomeration during mixing, affecting flame retardant performance, and the existing polyester fiber materials lack flame retardant performance at high temperatures.

Method used

Polyester slices, modified flame retardant and modified aramid fibers are used as raw materials to prepare flame retardant polyester fibers with good antibacterial properties and flame retardant properties through blending and extrusion and spinning processes. The modified flame retardant is added with cyclic phosphate, pentaerythritol, melamine, acrylate and modified nano zinc oxide. The modified aramid fiber is modified by dopamine to improve its surfactant functional groups.

Benefits of technology

The efficient preparation of flame-retardant polyester fiber is achieved, which improves its flame retardant and antibacterial properties, avoids flame retardant agglomeration, and improves the water resistance and durability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention belongs to the technical field of polyester fiber manufacturing, and particularly relates to a flame-retardant polyester fiber and a preparation method thereof. The flame-retardant polyester material is obtained by melt blending and spinning polyester slices, flame retardants and modified aramid fibers as raw materials. The flame retardant interacts with cyclic phosphate as an acid source, melamine as a gas source and pentaerythritol as a carbon source. When heated, the decomposition product has a strong dehydration effect, which can carbonize the surface of the covered polymer to form a carbon film, isolate the air, and prevent the polymer from continuing to burn, so that the flame-retardant polyester fiber has good flame retardant properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyester fiber manufacturing, and particularly relates to a flame-retardant polyester fiber and a preparation method thereof. Background Art

[0002] Chinese patent application number 202311045493.6 discloses a high temperature resistant flame retardant polyester fiber and a preparation process, wherein PET polyester chips, nitrogen phosphorus silicon polymer flame retardant containing DOPO, maleimide and siloxane structure are mixed evenly, extruded by blending, and then cut into pellets to obtain flame retardant PET pellets; PET polyester chips and flame retardant PET pellets are melt-spun on a spinning machine to obtain high temperature resistant flame retardant polyester fibers; Chinese patent application number 202110253948.8 ... Chinese patent application number 202311045493.6 discloses a high temperature resistant flame retardant polyester fiber and a preparation process, wherein PET polyester chips, nitrogen phosphorus silicon polymer flame retardant containing DOPO, maleimide and siloxane structure are mixed evenly, extruded by blending, and then cut into pellets to obtain flame retardant PET pellets; Chinese patent application number 202311045493.6 discloses a high temperature resistant flame retardant polyester fiber and a preparation process, wherein PET polyester chips, nitrogen The Chinese patent discloses a flame-retardant polyester fiber and its preparation process, which is prepared from polyester chips, flame-retardant masterbatch and anti-drip agent. The porous nanomaterial introduced therein is made of nano-grade sodium montmorillonite, water glass solution and sodium bicarbonate, etc., and each raw material is fully dispersed by ultrasonic dispersion, and then processed by natural precipitation and other processes; the final composite flame retardant not only has the flame retardant properties of nano zinc borate, but also has the flame retardant effect of sodium montmorillonite, so that it has better flame retardant properties than traditional flame retardants. At the same time, it also has certain water resistance and durability. However, the above raw materials are directly added during the mixing process, which is easy to agglomerate and thus affect the performance. Therefore, how to prepare polyester fiber materials with good flame retardant properties has become a hot topic of research. Summary of the invention

[0003] In order to solve the problems existing in the prior art, the present invention provides a flame-retardant polyester fiber and a preparation method thereof. The flame-retardant polyester fiber prepared by using polyester chips, flame retardant and modified aramid fiber as raw materials has good antibacterial and flame retardant properties.

[0004] The technical solution of the present invention to solve the above problems is as follows:

[0005] A flame retardant polyester fiber, characterized in that it comprises the following raw materials in parts by weight: 65-85 parts of polyester chips, 12-18 parts of flame retardants and 20-28 parts of modified aramid fibers, preferably 75 parts of polyester chips, 16 parts of flame retardants and 22 parts of modified aramid fibers.

[0006] The flame retardant is composed of cyclic phosphate, pentaerythritol, melamine, acrylate and modified nano zinc oxide; wherein the mass ratio of cyclic phosphate, pentaerythritol, melamine, acrylate and modified nano zinc oxide in the flame retardant is 20-28:6-8:1:35-45:10-16, and preferably the mass ratio of cyclic phosphate, pentaerythritol, melamine, acrylate and modified nano zinc oxide is 24:7:1:40:12.

[0007] The flame retardant interacts with cyclic phosphate as the acid source, melamine as the gas source, and pentaerythritol as the carbon source. When heated, the decomposition products have a strong dehydrating effect, which can carbonize the surface of the covered polymer to form a carbon film, isolate the air, and prevent the polymer from continuing to burn; pentaerythritol can be carbonized by the acid source during the combustion process, improve the carbonization stability, and enhance the flame retardant effect; melamine releases nitrogen-containing compounds of inert gas when decomposed by heat, which promotes the formation of a carbonized layer.

[0008] The preparation process of the modified aramid fiber is as follows: immersing the cleaned aramid fiber in a dopamine solution, leaving it for 18-28 hours, taking out the fiber, washing it and drying it; the drying condition is 50-65° C. for 4-6 hours.

[0009] Furthermore, the cleaning process of the aramid fiber is as follows: the aramid fiber is placed in a reactor, ultrasonically cleaned with anhydrous ethanol for 20-40 minutes, washed with deionized water for 3-5 times, and then placed in an oven for drying; the drying conditions are 50-65° C. and dried for 4-6 hours.

[0010] Furthermore, the preparation process of the dopamine solution is as follows: put dopamine hydrochloride granules powder into deionized water, stir until completely dissolved, the solution concentration is 2-4g / L, and add Tris buffer to adjust the pH to 8.5.

[0011] Aramid fiber includes amide bonds and aromatic rings in its macromolecular chain, has good heat resistance and low thermal expansion coefficient, but due to its high crystallinity and the steric hindrance of the benzene ring, the fiber surface is smooth, the active functional groups are few, the reaction activity is low, and the adhesion to most polymer matrices is poor, so dopamine is used to modify it in the present invention. Dopamine contains catechol groups and amino groups in its molecular structure, and can undergo oxidative self-polymerization in alkaline solution and oxygen-containing conditions to generate polydopamine, which strongly adheres to the material surface through intermolecular interactions such as covalent bonds, π-π bonds, and hydrogen bonds. The abundant phenolic hydroxyl and amino active functional groups in the polydopamine layer can effectively improve the surface properties of aramid fiber and further react with other active sites as active sites for secondary reactions.

[0012] Furthermore, the preparation process of the modified nano zinc oxide is as follows: ultrasonically dispersing the nano zinc oxide in deionized water, adjusting the pH to 6.5, adding vinyl triethoxysilane thereto, raising the temperature to 70-90°C for constant temperature reaction for 2-4 hours, then adding methacrylic acid, ammonium persulfate and sodium bisulfite aqueous solution thereto for reaction for 4-6 hours, cooling to room temperature, washing with deionized water, and freeze-drying to obtain the modified nano zinc oxide; wherein the amount of nano zinc oxide in deionized water is 8-15 g / L, and the amount in the sodium bisulfite aqueous solution is 1-4 g / L, wherein the mass ratio of nano zinc oxide, vinyl triethoxysilane, methacrylic acid, ammonium persulfate and sodium bisulfite is 1:0.2-0.6:1-3:0.2-0.4:0.1-0.3.

[0013] Nano zinc oxide has a char-promoting property, acts as an insulator between fabric and flame, and cooperates with flame retardants to improve the flame retardant effect. At the same time, nano zinc oxide can produce active oxygen and zinc ions, which have the effect of killing or preventing bacterial growth; however, nanoparticles are prone to agglomeration, which is not conducive to fully exerting their performance. Therefore, in the present invention, vinyl triethoxysilane is used to modify nano zinc oxide, double bonds are introduced on the surface of the nanoparticles, and nano zinc oxide containing carboxyl groups on the surface is prepared by free radical polymerization with acrylic acid; further, it is chemically reacted with modified aramid fibers, thereby introducing nano zinc oxide on the surface of the modified aramid fibers and improving the dispersion performance of nano zinc oxide.

[0014] The present invention also provides a method for preparing a flame retardant polyester fiber, comprising the following steps:

[0015] S1, weighing each raw material according to the above weight parts;

[0016] S2, after mixing the modified aramid fiber and the flame retardant, adding tetrabutyl titanate thereto and raising the temperature to 90-105° C., reacting for 2-4 hours, naturally cooling to room temperature, and drying to obtain a composite product of the modified aramid fiber and the flame retardant; wherein the mass ratio of tetrabutyl titanate to the modified aramid fiber is 1:8-12;

[0017] S3, adding the dried polyester slices and the composite product prepared in step S2 into a high-speed mixer for thorough mixing, and then feeding the resulting mixture into a screw extruder for melt extrusion; wherein the stirring condition is 200-600 r / min for 30-60 min;

[0018] S4. The melt extruded from the screw extruder passes through the spinneret of the spinning assembly, is spun into shape at a spinning speed of 200-220 m / min and a winding speed of 700-900 m / min, and is heat-set at 165-185° C. to obtain the flame-retardant polyester fiber.

[0019] Furthermore, the moisture content of the composite product of the modified aramid fiber and the flame retardant after drying in step S2 is ≤120 ppm, and the moisture content of the polyester chips after drying in step S3 is ≤40 ppm.

[0020] The present invention has the following beneficial effects:

[0021] In the present invention, the flame retardant uses cyclic phosphate as an acid source, melamine as a gas source, and pentaerythritol as a carbon source to interact with each other, decomposes when heated to produce a product with a strong dehydration effect, and carbonizes the surface of the covered polymer to form a carbon film to isolate the air and prevent the polymer from continuing to burn. In addition, modified nano zinc oxide is added to the flame retardant. The nano zinc oxide has a coke-promoting property, acts as an insulator between the fabric and the flame, and synergizes with other components in the flame retardant to improve the flame retardant effect; however, nano particles are prone to agglomeration, so in the present invention, vinyl triethoxysilane is used to modify the nano zinc oxide, double bonds are introduced on the surface of the nano particles, and nano zinc oxide containing carboxyl groups on the surface is prepared by free radical polymerization with acrylic acid to promote the dispersion of nano zinc oxide; further, modified aramid fiber is introduced in the present invention, and by modifying it with dopamine, the surface properties of the aramid fiber can be effectively improved, and more active reaction sites such as phenolic hydroxyl groups and amino active groups are introduced on its surface, and chemical reactions occur with the modified nano zinc oxide in the further preparation process, further promoting the dispersion of nano zinc oxide. Aramid fiber has amide bonds and aromatic rings in its macromolecular chain, and has good heat resistance and low thermal expansion coefficient. Therefore, when it is blended with polyester chips, it can play a supporting role because its decomposition temperature is much higher than that of polyester and it will not melt. During the combustion process, a large number of molten droplets produced by polyester will adhere to its surface with the undecomposed special fibers as a support, effectively reducing the dripping of molten droplets; and the large amount of dense coke produced by its decomposition can provide a secondary support for the polyester melt, preventing the molten droplets from falling while accelerating the carbonization of the polyester molten droplets, thereby increasing the carbonization rate. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0023] Polyester chips were purchased from Yuyao Jujing Plastic Chemical Co., Ltd., cyclic phosphate was purchased from Xusen Halogen-free Smoke Retardant Co., Ltd., pentaerythritol and melamine were purchased from Sinopharm Chemical Reagent Co., Ltd., acrylate (BLJ-733D self-crosslinked anionic emulsion, industrial grade) was purchased from Shanghai Baolijia Chemical, and aramid fiber was purchased from Sichuan Chengdu Chenguang Co., Ltd. (aramid III fiber, diameter 14 μm, density 1.44 g / cm 3 , linear density of 1.1483 g / m), dopamine hydrochloride was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (purity 98%), SBF simulated body fluid was purchased from Kandis Chemical (Hubei) Co., Ltd., and the reagents used in the present invention were all commercially available.

[0024] Example 1

[0025] A flame retardant polyester fiber comprises the following raw materials in parts by weight: 75 parts of polyester chips, 16 parts of flame retardants and 22 parts of modified aramid fibers.

[0026] The flame retardant is composed of cyclic phosphate, pentaerythritol, melamine, acrylate and modified nano zinc oxide, and the mass ratio of cyclic phosphate, pentaerythritol, melamine, acrylate and modified nano zinc oxide is 24:7:1:40:12.

[0027] The preparation process of the modified aramid fiber is as follows: immerse the cleaned aramid fiber in a dopamine solution, take out the fiber after leaving it for 24 hours, wash it with deionized water for 3 times, and then place it in an oven at 55°C to dry for 5 hours.

[0028] The cleaning process of the aramid fiber is as follows: the aramid fiber is placed in a reactor, ultrasonically cleaned with anhydrous ethanol for 30 minutes, washed with deionized water for 3 times, and then placed in an oven and dried at 55° C. for 5 hours.

[0029] The preparation process of the dopamine solution is as follows: put dopamine hydrochloride granules powder into deionized water, stir until completely dissolved to obtain a solution concentration of 3g / L, and add Tris buffer to adjust the pH to 8.5.

[0030] The preparation process of modified nano zinc oxide is as follows: ultrasonically disperse nano zinc oxide in deionized water, add dilute hydrochloric acid to adjust the pH to 6.5, add vinyl triethoxysilane, raise the temperature to 80°C and react at a constant temperature for 3 hours, then add methacrylic acid, ammonium persulfate and sodium bisulfite aqueous solution to react for 5 hours, cool to room temperature, wash with deionized water for 3 times, and freeze-dry to obtain the modified nano zinc oxide; the amount of nano zinc oxide in deionized water is 10 g / L, the concentration of dilute hydrochloric acid is 1 mol / L, the amount in the sodium bisulfite aqueous solution is 2 g / L, and the mass ratio of nano zinc oxide, vinyl triethoxysilane, methacrylic acid, ammonium persulfate and sodium bisulfite is 1:0.4:2:0.3:0.2.

[0031] A method for preparing a flame-retardant polyester fiber comprises the following steps:

[0032] S1, weighing each raw material according to the above weight parts;

[0033] S2. After the modified aramid fiber and the flame retardant are mixed, tetrabutyl titanate is added thereto and the temperature is raised to 95° C. After reacting for 3 hours, the mixture is naturally cooled to room temperature and vacuum dried to obtain a composite product of the modified aramid fiber and the flame retardant; wherein the mass ratio of tetrabutyl titanate to the modified aramid fiber is 1:10; and the moisture content of the composite product of the modified aramid fiber and the flame retardant after drying is ≤120ppm;

[0034] S3, the dried polyester chips and the composite product prepared in step S2 are put into a high-speed mixer for thorough mixing, and then the obtained mixture is fed into a screw extruder for melt extrusion; wherein the stirring condition is 400r / min for 40min; wherein the moisture content of the dried polyester chips is ≤40ppm;

[0035] S4. The melt extruded from the screw extruder passes through the spinneret of the spinning assembly, is spun into shape at a spinning speed of 210 m / min and a winding speed of 800 m / min, and is heat-set at 175° C. to obtain a flame-retardant polyester fiber.

[0036] Example 2

[0037] Compared with Example 1, this embodiment has the following differences, and the rest of the process refers to Example 1.

[0038] A flame retardant polyester fiber comprises the following raw materials in parts by weight: 65 parts of polyester chips, 12 parts of flame retardants and 20 parts of modified aramid fibers, wherein the mass ratio of cyclic phosphate, pentaerythritol, melamine, acrylate and modified nano zinc oxide in the flame retardant is 20:6:1:35:10.

[0039] In the preparation process of modified aramid fiber, the cleaned aramid fiber is placed in the dopamine solution for 18 hours, washed with deionized water for 3 times, and dried in an oven at 50°C for 4 hours. In the cleaning process of the aramid fiber, it is ultrasonically cleaned with anhydrous ethanol for 20 minutes, washed with deionized water for 3 times, and then dried at 50°C for 4 hours; in the preparation process of the dopamine solution, the concentration of the prepared solution is 2g / L.

[0040] In the preparation process of modified nano zinc oxide, vinyl triethoxysilane is added thereto, the temperature is raised to 70°C, the reaction is carried out at a constant temperature for 2 hours, and then methacrylic acid, ammonium persulfate and sodium bisulfite aqueous solution are added thereto to react for 4 hours; the amount of nano zinc oxide in deionized water is 8 g / L, and the amount in the sodium bisulfite aqueous solution is 1 g / L, and the mass ratio of nano zinc oxide, vinyl triethoxysilane, methacrylic acid, ammonium persulfate and sodium bisulfite is 1:0.2:1:0.2:0.1.

[0041] A method for preparing flame-retardant polyester fiber comprises the following steps: in step S2, tetrabutyl titanate is added and the temperature is raised to 90° C., and the reaction is carried out for 2 hours; the mass ratio of tetrabutyl titanate to modified aramid fiber is 1:8; in step S3, the stirring condition is 200 r / min for 30 minutes; in step S4, the fiber is spun at a spinning speed of 200 m / min and a winding speed of 700 m / min, and heat-set at 165° C.

[0042] Example 3

[0043] Compared with Example 1, this embodiment has the following differences, and the rest of the process refers to Example 1.

[0044] A flame retardant polyester fiber comprises the following raw materials in parts by weight: 85 parts of polyester chips, 18 parts of flame retardants and 28 parts of modified aramid fibers, wherein the mass ratio of cyclic phosphate, pentaerythritol, melamine, acrylate and modified nano zinc oxide in the flame retardant is 28:8:1:45:16.

[0045] In the preparation process of modified aramid fiber, the cleaned aramid fiber is placed in a dopamine solution for 28 hours, washed with deionized water for 5 times, and dried in an oven at 65°C for 6 hours. In the cleaning process of the aramid fiber, it is ultrasonically cleaned with anhydrous ethanol for 40 minutes, washed with deionized water for 5 times, and then dried at 65°C for 6 hours; in the preparation process of the dopamine solution, the concentration of the prepared solution is 4g / L.

[0046] In the preparation process of modified nano zinc oxide, vinyl triethoxysilane is added thereto and the temperature is raised to 90°C, and the reaction is carried out at a constant temperature for 4 hours, and then methacrylic acid, ammonium persulfate and sodium bisulfite aqueous solution are added thereto and reacted for 6 hours; the amount of nano zinc oxide in deionized water is 15 g / L, and the amount in the sodium bisulfite aqueous solution is 4 g / L, and the mass ratio of nano zinc oxide, vinyl triethoxysilane, methacrylic acid, ammonium persulfate and sodium bisulfite is 1:0.6:3:0.4:0.3.

[0047] A method for preparing flame-retardant polyester fiber comprises the following steps: in step S2, tetrabutyl titanate is added and the temperature is raised to 105°C, and the reaction is carried out for 4 hours; the mass ratio of tetrabutyl titanate to modified aramid fiber is 1:12; in step S3, the stirring condition is 600 r / min for 60 minutes; in step S4, the fiber is spun at a spinning speed of 220 m / min and a winding speed of 900 m / min, and heat-set at 185°C.

[0048] Comparative Example 1

[0049] Compared with Example 1, in this comparative example, the aramid fiber is not modified during the preparation process, and the aramid fiber is directly added. The rest of the process refers to Example 1.

[0050] A flame retardant polyester fiber comprises the following raw materials in parts by weight: 75 parts of polyester chips, 16 parts of flame retardants and 22 parts of aramid fibers.

[0051] A method for preparing flame-retardant polyester fiber comprises the following steps: in step S2, aramid fiber and a flame retardant are mixed, the temperature is raised to 95° C., the mixture reacts for 3 hours, the mixture is naturally cooled to room temperature, and the composite product of aramid fiber and flame retardant is obtained after vacuum drying.

[0052] Comparative Example 2

[0053] Compared with Example 1, in this comparative example, nano zinc oxide is not modified during the preparation of the flame retardant, and nano zinc oxide is directly added. The rest of the process is the same as Example 1.

[0054] The flame retardant is composed of cyclic phosphate, pentaerythritol, melamine, acrylate and nano zinc oxide, and the mass ratio of cyclic phosphate, pentaerythritol, melamine, acrylate and nano zinc oxide is 24:7:1:40:12.

[0055] A method for preparing flame-retardant polyester fiber comprises the following steps: in step S2, the modified aramid fiber and the flame retardant are mixed, the temperature is raised to 95° C., the mixture reacts for 3 hours, the mixture is naturally cooled to room temperature, and the composite product of the modified aramid fiber and the flame retardant is obtained after vacuum drying.

[0056] Comparative Example 3

[0057] Compared with Example 1, this comparative example does not add modified aramid fiber during the preparation process, and does not add modified nano zinc oxide during the preparation process of the flame retardant. The remaining processes refer to Example 1.

[0058] A flame-retardant polyester fiber comprises the following raw materials in parts by weight: 75 parts of polyester chips and 16 parts of flame retardants; wherein the flame retardants are composed of cyclic phosphate ester, pentaerythritol, melamine and acrylate, and the mass ratio of the cyclic phosphate ester, pentaerythritol, melamine and acrylate is 24:7:1:40.

[0059] A method for preparing a flame-retardant polyester fiber comprises the following steps: weighing the raw materials according to the above weight parts, adding the dried polyester slices and the flame retardant into a high-speed mixer for full mixing, and then feeding the obtained mixture into a screw extruder for melt extrusion; wherein the stirring condition is 400r / min stirring for 40min; the moisture content of the dried polyester slices is ≤40ppm; the melt extruded by the screw extruder passes through the spinneret of a spinning assembly, is spun into shape at a spinning speed of 210m / min and a winding speed of 800m / min, and is heat-set at 175°C to obtain the flame-retardant polyester fiber.

[0060] Related tests:

[0061] The flame-retardant polyester fibers prepared in Examples 1-3 and Comparative Examples 1-3 were made into fiber fabrics and relevant performance tests were performed.

[0062] 1. Limiting oxygen index test: The standard specimens were pressed using the S(X)LB-350×350-25 flat plate vulcanizer produced by Changzhou Suyan Technology Co., Ltd. The test was performed using the HC-2CZ limiting oxygen index tester produced by Nanjing Shangyuan Analytical Instrument Co., Ltd. in accordance with the ASTM D2863 standard. The test results are shown in Table 1.

[0063] Table 1 Limiting oxygen index test results

[0064] sample Limiting oxygen index (LOI) / % Example 1 48.5 Example 2 46.8 Example 3 46.2 Comparative Example 1 38.6 Comparative Example 2 36.4 Comparative Example 3 32.4

[0065] The limiting oxygen index refers to the percentage of the minimum O2 volume concentration required for a sample to maintain a complete combustion state in a mixture of O2 and N2. The larger the LOI value, the better the flame retardant performance of the material. From the above test results, it can be seen that the LOI values ​​of the samples of Examples 1-3 are higher than those of Comparative Examples 1-3, especially the LOI value of Example 1 is the highest; from the comparison of the test results of Example 1 and Comparative Example 1 (without modification of the aramid fiber), it can be seen that the surface properties of the aramid fiber can be effectively improved by surface modification of the aramid fiber, and the combination between the aramid fiber and other raw materials can be promoted, thereby improving the limiting oxygen index of the test sample; from the comparison of Example 1 and Comparative Example 2 (without modification of nano zinc oxide), it can be seen that the modified nano zinc oxide can effectively promote the dispersion of nano zinc oxide and prevent agglomeration.

[0066] 2. Vertical combustion (UL-94) test: CZF-2 vertical combustion tester (Nanjing, China) was used to test the sample according to GB / T2408-2008 "Horizontal and vertical methods for the determination of combustion performance of plastics". The sample size is 130mm×13mm×3mm. The test method is to fix the sample vertically to the sample clamp, with the clamped part at the upper end being 6mm, and the distance between the lower end of the sample and the absorbent cotton (6mm thick) being 300mm. A Bunsen burner (flame height 20mm, blue flame) was used to apply flame to the sample at a distance of 150mm from the bottom of the sample for 10s and then removed, and the test data of the sample was recorded. After the sample burned out, it was ignited again according to the above method, and the test data were recorded respectively. The test standards are shown in Table 2, and the test results are shown in Table 3.

[0067] Table 2 Test standards

[0068]

[0069]

[0070] Table 3 Test results

[0071]

[0072] It can be seen from the test results in Table 3 that the samples prepared in Examples 1-3 all reached the V-0 level, especially the sample prepared in Example 1 self-extinguished within 1 second after the first ignition and the second ignition, reaching the V-0 level; this is because the decomposition products of the flame retardant have a strong dehydrating effect when heated, which can carbonize the covered polymer surface, forming a carbon film to isolate the air and prevent the polymer from continuing to burn; and during the combustion process, the modified aramid fiber can provide a support to adhere to a large number of molten droplets produced by polyester, effectively preventing the molten droplets from dripping.

[0073] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0074] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A flame retardant polyester fiber, characterized in that: The invention comprises the following raw materials in parts by weight: 65-85 parts of polyester chips, 12-18 parts of flame retardant and 20-28 parts of modified aramid fiber; The flame retardant is composed of cyclic phosphate, pentaerythritol, melamine, acrylate and modified nano zinc oxide; The preparation process of the modified aramid fiber is as follows: immersing the cleaned aramid fiber in a dopamine solution, leaving it for 18-28 hours, taking out the fiber, washing it, and drying it; The method for preparing the flame-retardant polyester fiber comprises the following steps: weighing the raw materials according to the above weight parts; mixing the modified aramid fiber with the flame retardant, adding tetrabutyl titanate thereto and raising the temperature to 90-105°C, reacting for 2-4 hours, naturally cooling to room temperature, and drying to obtain a composite product of the modified aramid fiber and the flame retardant; adding the dried polyester slices and the composite product obtained in step S2 into a high-speed mixer for thorough mixing, and then feeding the obtained mixture into a screw extruder for melt extrusion; passing the melt extruded by the screw extruder through a spinneret of a spinning assembly, spinning at a spinning speed of 200-220 m / min and a winding speed of 700-900 m / min, and heat setting at 165-185°C to obtain the flame-retardant polyester fiber.

2. The flame-retardant polyester fiber according to claim 1, characterized in that: The cleaning process of the aramid fiber is as follows: the aramid fiber is placed in a reactor, ultrasonically cleaned with anhydrous ethanol, then washed with deionized water, and then placed in an oven for drying.

3. The flame-retardant polyester fiber according to claim 1, characterized in that: The preparation process of the dopamine solution is as follows: put dopamine hydrochloride granules powder into deionized water, stir until it is completely dissolved, and add Tris buffer to adjust the pH to 8.

5.

4. The flame-retardant polyester fiber according to claim 1, characterized in that: The preparation process of the modified nano zinc oxide is as follows: ultrasonically dispersing the nano zinc oxide in deionized water, adjusting the pH to 6.5, adding vinyl triethoxysilane, raising the temperature to 70-90° C. and reacting at a constant temperature for 2-4 hours, then adding methacrylic acid, ammonium persulfate and sodium bisulfite aqueous solution and reacting for 4-6 hours, cooling to room temperature, washing with deionized water, and freeze-drying to obtain the modified nano zinc oxide.

5. The flame-retardant polyester fiber according to claim 1, characterized in that: The mass ratio of cyclic phosphate, pentaerythritol, melamine, acrylate and modified nano zinc oxide in the flame retardant is 20-28:6-8:1:35-45:10-16.

6. The method for preparing a flame-retardant polyester fiber according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, weighing each raw material according to the above weight parts; S2, after mixing the modified aramid fiber and the flame retardant, adding tetrabutyl titanate thereto and raising the temperature to 90-105° C., reacting for 2-4 hours, naturally cooling to room temperature, and drying to obtain a composite product of the modified aramid fiber and the flame retardant; S3, putting the dried polyester slices and the composite product prepared in step S2 into a high-speed mixer for thorough mixing, and then feeding the obtained mixture into a screw extruder for melt extrusion; S4. The melt extruded from the screw extruder passes through the spinneret of the spinning assembly, is spun into shape at a spinning speed of 200-220 m / min and a winding speed of 700-900 m / min, and is heat-set at 165-185° C. to obtain the flame-retardant polyester fiber.

7. The method for preparing the flame-retardant polyester fiber according to claim 6, characterized in that: The moisture content of the composite product of the modified aramid fiber and the flame retardant after drying in step S2 is ≤120 ppm, and the moisture content of the polyester chips after drying in step S3 is ≤40 ppm.

Citation Information

Patent Citations

  • High-temperature-resistant flame-retardant polyester fiber and preparation process thereof

    CN116770453A

  • Fire-resistant antibacterial curtain fabric and preparation method thereof

    CN111519308A

  • Flame-retardant polyester fiber and preparation process thereof

    CN112831863A